Literature Review of Public Administration and Good Governance from 1890 to 2023 - Lance Barbier; Robertson Tengeh (Jurnal Transformative, 2023)
This article examines public administration from 1890 to 2023 to see how it evolved and influenced practice and if good governance is a crucial component in this transformation. This paper presents an in-depth review of several different pieces of secondary literature sources. This paper produced several key findings. The most important finding of this literature study is that, between 1890 and 1980, the Public Administration transitioned from "Traditional Public Administration" to "New Public Management" due to the growing need for good governance. The year 2000 saw the birth of a novel idea in public administration known as "New Public Governance," which has persisted in practice ever since. This paper will be useful to Public Administration practitioners worldwide. There has been little empirical research into how the evolution of Public Administration encourages governments to act more like private corporations. Consequently, more research on this subject is encouraged.